Visual auditory kinesthetic learning model as a strategy to enhance senior high school students’ learning motivation in Islamic education - Saidah, Elbina Mamla; Pratiwi, Eka Aprilia; Lisa, Hendro; Suhada, Suhada; Ramli, Efni (UIR Press, 2026)
Learning motivation remains a significant challenge in Islamic education and character education, where teacher-centred instruction often limits students' engagement and participation. Although the visual auditory kinesthetic (VAK) learning model has been widely implemented, its role as a motivational pedagogical framework has received limited empirical attention. This study aimed to examine the effectiveness of the VAK learning model in enhancing senior high school students' learning motivation by conceptualising it as a multimodal instructional strategy integrating visual, auditory, and kinesthetic learning experiences. A quantitative quasi-experimental design with a non-equivalent control group was employed. The participants comprised 53 Grade XI students from a public senior high school in Riau, Indonesia, including 27 students in the experimental group and 26 students in the control group. Data were collected using a validated learning motivation questionnaire administered before and after the intervention and analysed using descriptive statistics and ANCOVA. The findings indicated that students receiving VAK-based instruction demonstrated significantly higher post-test motivation than those receiving conventional instruction, with an adjusted mean difference of 18.06 points and a large practical effect. The study's novelty lies in reconceptualising VAK as a motivational framework that promotes competence, relatedness, and autonomy through multimodal learning. However, the findings are limited by the small sample from a single school and the use of short-term self-reported motivation measures. The results suggest that structured multimodal instruction can foster more engaging, learner-centred Islamic Education classrooms.